Method for producing sintered silicon nitride
The silicon nitride sintered body addresses the challenge of achieving both high thermal conductivity and reliability by controlling grain growth through a low gelatinization rate, resulting in improved heat dissipation and stability for power modules.
Patent Information
- Application Number
- JP2021511943
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-03-26
AI Technical Summary
Conventional ceramic substrates used in power modules struggle to achieve both excellent heat dissipation and high reliability, particularly when subjected to thermal cycles.
A silicon nitride sintered body is manufactured with a gelatinization rate of silicon nitride in the raw material powder of 30% by mass or less, promoting controlled grain growth and reducing defects, resulting in high thermal conductivity and fracture toughness.
The silicon nitride sintered body exhibits thermal conductivity exceeding 100 W/m K and fracture toughness of 7.4 MPa m 1/2, enhancing heat dissipation and reliability, making it suitable for power modules.
Smart Images

Figure 0007611816000004 
Figure 0007611816000005 
Figure 0007611816000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a silicon nitride sintered body and a method for producing the same, as well as a laminate and a power module. [Background technology]
[0002] Power modules that control large currents are used in the fields of automobiles, electric railways, industrial equipment, and power generation. Ceramic substrates are used as insulating substrates mounted on power modules. In such applications, ceramic substrates are required to have good heat dissipation characteristics in addition to insulation properties. For example, Patent Document 1 proposes a ceramic substrate made of a material mainly composed of aluminum nitride, alumina, silicon nitride, or silicon carbide.
[0003] Furthermore, Patent Document 2 proposes a technique for producing a silicon nitride sintered body having a thermal conductivity of 100 W / (m K) or more at room temperature by adding rare earth elements and Mg as sintering aid components and carrying out a heat treatment under specific conditions. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-212316 A [Patent Document 2] JP 2006-96661 A Summary of the Invention [Problem to be solved by the invention]
[0005] Power modules are important components that control various devices, and therefore they are required to function stably. To improve stability, it is necessary not only to ensure the reliability of each component that constitutes the power module, but also to suppress the heat generated by large currents. To meet these requirements, it is considered useful to have a ceramic substrate that has excellent heat dissipation properties and does not easily break down even with increased thermal cycles. However, with conventional ceramic substrates, it has been difficult to achieve both excellent heat dissipation properties and high reliability.
[0006] In view of this, the present disclosure provides a silicon nitride sintered body having both excellent heat dissipation properties and high reliability, and a method for producing the same. The present disclosure also provides a laminate including such a silicon nitride sintered body. The present disclosure also provides a laminate including the above-mentioned laminate. Power Module to provide. [Means for solving the problem]
[0007] A method for producing a silicon nitride sintered body according to one aspect of the present disclosure includes forming and sintering a raw material powder containing silicon nitride, and the silicon nitride contained in the raw material powder has an alpha-phase rate of 30 mass% or less. In this production method, a raw material powder having an alpha-phase rate of 30 mass% or less is used. When the alpha-phase rate of silicon nitride in the raw material powder is high, the grain growth rate tends to increase in the sintering step. In this case, although sintering is promoted, it is considered that the number of defects remaining in the obtained sintered body increases.
[0008] On the other hand, when the alpha-conversion rate of silicon nitride in the raw material powder is low, the beta-conversion rate in the raw material powder is high, and the grain growth rate in the sintering process tends to be slow. In this case, although sintering takes time, it is considered that the defects contained in the obtained sintered body are reduced and the thermal conductivity and fracture toughness are improved. Due to this action, the silicon nitride sintered body obtained by the above manufacturing method can be manufactured to have both excellent heat dissipation properties and high reliability.
[0009] The thermal conductivity (20℃) of the silicon nitride sintered body obtained by the above-mentioned manufacturing method exceeds 100 W / m K, and the fracture toughness (K IC ) is 7.4 MPa m 1 / 2 The flexural strength of the silicon nitride sintered body obtained by the above-mentioned production method may be more than 600 MPa. By having such characteristics, the heat dissipation property and reliability are further improved, and it can be used more preferably as a substrate for a power module, for example.
[0010] The silicon nitride sintered body according to one aspect of the present disclosure has a thermal conductivity (20°C) of more than 100 W / m K and a fracture toughness (K IC ) is 7.4MPa m 1 / 2 This silicon nitride sintered body has high thermal conductivity and fracture toughness, and therefore has both excellent heat dissipation and high reliability. For this reason, it can be suitably used, for example, as a substrate for a power module.
[0011] The silicon nitride sintered body may have a flexural strength of more than 600 MPa. Such a characteristic further improves the reliability, making it more suitable for use as a substrate for a power module, for example.
[0012] The thermal conductivity of the silicon nitride sintered body at 150 to 200° C. may exceed 60 W / m·K, making it even more suitable for use as a substrate for power modules used under particularly harsh conditions.
[0013] A laminate according to one aspect of the present disclosure includes a metal layer made of a first metal, a heat dissipation section made of a second metal having a higher thermal conductivity than the first metal, and a substrate provided between the metal layer and the heat dissipation section and made of any of the above-mentioned silicon nitride sintered bodies. The substrate of this laminate is made of a silicon nitride sintered body having both excellent heat dissipation properties and high reliability. The substrate is provided between the metal layer and the heat dissipation section. Therefore, heat generated on the metal layer side can be efficiently dissipated from the heat dissipation section side. Therefore, the laminate can be suitably used as a laminate for a power module, for example.
[0014] A power module according to an aspect of the present disclosure includes the laminate described above and a semiconductor element electrically connected to the metal layer. Such a power module has excellent heat dissipation properties and reliability due to the inclusion of the substrate described above. Effect of the Invention
[0015] According to the present disclosure, it is possible to provide a silicon nitride sintered body having both excellent heat dissipation properties and high reliability, and a method for producing the same. In addition, according to the present disclosure, it is possible to provide a laminate including such a silicon nitride sintered body. In addition, according to the present disclosure, it is possible to provide a laminate including the above-mentioned laminate. Power Module can be provided. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view of one embodiment of a power module. [Diagram 2] FIG. 2 is a schematic diagram showing grain growth during sintering of silicon nitride particles in one embodiment of a method for producing a silicon nitride sintered body. [Diagram 3] FIG. 3 is a graph showing the relationship between the firing temperature and the relative density. [Figure 4] FIG. 4 is a graph showing the temperature change in thermal conductivity of the silicon nitride sintered bodies of Example 1 and Comparative Example 1. [Diagram 5] FIG. 5 is an electron microscope photograph of a fracture surface of the silicon nitride sintered body of Example 1. [Figure 6] FIG. 6 is a schematic diagram showing grain growth during sintering of silicon nitride particles in a conventional method for producing a silicon nitride sintered body. [Figure 7] FIG. 7 is an electron microscope photograph of a fracture surface of the silicon nitride sintered body of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described with reference to the drawings as needed. However, the following embodiment is merely an example for explaining the present invention, and is not intended to limit the present invention to the following content. In the description, the same reference numerals are used for the same elements or elements having the same functions, and redundant description is omitted as the case may be. The dimensional ratio of each element is not limited to the ratio shown in the drawings.
[0018] The silicon nitride sintered body according to one embodiment has a thermal conductivity of more than 100 W / m·K at 20° C. The thermal conductivity (20° C.) in the present disclosure can be measured in accordance with JIS R 1611:2010. This thermal conductivity (20° C.) is calculated by multiplying the thermal diffusivity A [m 2 / sec], density B[kg / m 3 The thermal diffusivity A is calculated from the values of the thermal conductivity, specific heat C [J / (kg K)], using the formula A × B × C. The thermal diffusivity A is calculated by the laser flash method using a sample with dimensions of length × width × thickness = 10 mm × 10 mm × 2 mm. Specifically, A = 0.1388 × (thickness [mm]) 2 / t 1 / 2 It can be calculated by the formula: t 1 / 2 is the time [seconds] required for the temperature to rise to half of the total temperature rise ΔT. Density B is calculated by Archimedes' law. Specific heat C is calculated by differential thermal analysis.
[0019] The thermal conductivity (20°C) of the silicon nitride sintered body may exceed 110 W / m K, 120 W / m K, or 140 W / m K, for example, from the viewpoint of further improving heat dissipation. The upper limit of the thermal conductivity (20°C) may be, for example, 200 W / m K, from the viewpoint of ease of production.
[0020] For example, from the viewpoint of sufficiently increasing the heat dissipation when used in a power module or the like, the thermal conductivity of the silicon nitride sintered body at 150 to 200°C may exceed 60 W / m·K, and may also exceed 65 W / m·K. From the viewpoint of ease of manufacture, the upper limit of the thermal conductivity at 150 to 200°C may be, for example, 150 W / m·K. The thermal conductivity in such a temperature range can also be calculated by the formula A×B×C as described above. In this case, the thermal diffusivity A is the measured value obtained by carrying out the above-mentioned measurement at the relevant temperature, and the specific heat C may be a literature value. The density B can be used as it is at 20°C.
[0021] Silicon nitride sintered body has a strength of 7.4 MPa m 1 / 2 Fracture toughness (K IC ) Fracture toughness (K IC ) is a value measured by the SEPB method and is measured in accordance with JIS R1607:2015. IC ) is set at 7.5MPa m from the viewpoint of further improving reliability. 1 / 2 may exceed 8MPa m 1 / 2 Fracture toughness (K IC ) is set at an upper limit of, for example, 15 MPa m from the viewpoint of ease of manufacturing. 1 / 2 It may be.
[0022] The silicon nitride sintered body may have a flexural strength of more than 600 MPa from the viewpoint of further improving reliability. The flexural strength is a three-point bending flexural strength, and can be measured using a commercially available flexural strength meter in accordance with JIS R 1601:2008. The flexural strength of the silicon nitride sintered body may be more than 620 MPa or more than 650 MPa from the viewpoint of further improving reliability. The upper limit of the flexural strength may be, for example, 800 MPa from the viewpoint of ease of production.
[0023] The silicon nitride sintered body may be substantially composed of silicon nitride alone, or may contain components derived from sintering aids and unavoidable components derived from raw materials and manufacturing processes, etc. The content of silicon nitride in the silicon nitride sintered body may be, for example, 90 mol % or more, 95 mol % or more, or 98 mol % or more, from the viewpoint of achieving both high thermal conductivity and excellent insulating properties at a high level.
[0024] Since the silicon nitride sintered body can be produced by using a small amount of sintering aid, the total content of rare earth elements in the silicon nitride sintered body can be sufficiently low. The total content of rare earth elements in the silicon nitride sintered body may be 6.0 mass% or less, or 3.0 mass% or less. The rare earth elements include 17 elements in total, including two elements, Sc (scandium) and Y (yttrium), and 15 lanthanoid elements from La (lanthanum) to Lu (lutetium).
[0025] The silicon nitride sintered body may have a dielectric breakdown strength of 10 [kV / 0.32 mm] or more. The dielectric breakdown strength can be measured in accordance with JIS C-2110:2016. The dielectric breakdown strength may be, for example, 11 [kV / 0.32 mm] or more. The upper limit of the dielectric breakdown strength may be, for example, 15 [kV / 0.32 mm] from the viewpoint of ease of manufacture.
[0026] 1 is a schematic cross-sectional view of a power module according to one embodiment. The power module 100 includes, in this order, a metal layer 11, a substrate 10 (sintered silicon nitride 10), a metal layer 12, a solder layer 32, a base plate 20, and a cooling fin 22. The metal layer 11 forms a metal circuit by, for example, etching. A semiconductor element 60 is attached to the metal layer 11 via the solder layer 31. The semiconductor element 60 is connected to a predetermined portion of the metal layer 11 by a metal wire 34 such as an aluminum wire.
[0027] The substrate 10 is made of a sintered silicon nitride. This electrically insulates the metal layer 11 and the metal layer 12. The metal layer 12 may or may not form an electric circuit. The materials of the metal layer 11 and the metal layer 12 may be the same or different. The metal layer 11 and the metal layer 12 may be made of copper, which corresponds to the first metal. However, the material is not limited to copper.
[0028] The metal layer 12 is bonded to the base plate 20 via a solder layer 32. The shape of the base plate 20 may be, for example, a substantially rectangular plate with dimensions of length×width×thickness=90-140 mm×120-200 mm×3-6 mm. Screws 23 are provided at the ends of the base plate 20 to fix the cooling fins 22, which serve as heat dissipation members, to the base plate. The base plate 20 may be made of aluminum, which corresponds to the second metal. The base plate 20 is bonded to the cooling fins 22 via grease 24 on the side opposite to the metal layer 12 side.
[0029] The base plate 20 and the cooling fins 22 function as a heat dissipation section by being made of a second metal having a higher thermal conductivity than the metal layer 11. Since the substrate 10 has a high thermal conductivity, the semiconductor element 60, the metal layer 11 and the metal layer 12 are efficiently cooled by the heat dissipation section.
[0030] A resin housing 36 is attached to one side of the base plate 20 (the side on which the semiconductor element 60 is installed) so as to house the above-mentioned components (semiconductor element 60, metal layers 11, 12, and substrate 10). The above-mentioned components are housed in a space formed by one side of the base plate 20 and the housing 36, and a filler 30 such as silicone gel is filled in the space to fill any gaps. To electrically connect the outside of the housing 36 to the metal layer 11, a predetermined portion of the metal layer 11 is connected to an electrode 33 provided penetrating the housing 36 via a solder layer 35.
[0031] The power module 100 includes a laminate 50 including a metal layer 11, a substrate 10, a metal layer 12, a base plate 20, and a cooling fin 22. The substrate 10 is made of a silicon nitride sintered body having both high thermal conductivity and high fracture toughness. Since the substrate 10 has high thermal conductivity, heat can be smoothly dissipated from the semiconductor element 60 and the metal layer 11 toward the substrate 10 and the cooling fin 22. The silicon nitride sintered body is not easily broken even when subjected to an impact. Therefore, the power module 100 can stably perform its performance and has excellent reliability. In this way, the silicon nitride sintered body is suitably used as a substrate for the power module 100. However, the use of the silicon nitride sintered body 10 is not limited to the power module.
[0032] The material of the base plate 20 is not limited to aluminum. For example, the base plate 20 may be made of a first metal (e.g., copper, etc.), and only the cooling fins may be made of a second metal (aluminum, etc.). In this case, only the cooling fins 22 function as a heat dissipation section. In another embodiment, the cooling fins 22 may not be provided, and only the base plate 20 may function as a heat dissipation section. In yet another embodiment, the metal layer 12 may not be provided, and the base plate 20 and the substrate 10 may be joined together.
[0033] A method for producing a silicon nitride sintered body will be described below. The method for producing a silicon nitride sintered body according to one embodiment includes a process for molding and sintering a raw material powder containing silicon nitride. The alpha conversion rate of silicon nitride contained in the raw material powder used is 30 mass% or less. This makes it possible to slow down the grain growth rate of silicon nitride in the sintering process. Therefore, although sintering takes time, it is possible to reduce defects remaining in the resulting silicon nitride sintered body.
[0034] The gelatinization rate of silicon nitride contained in the raw material powder may be 20 mass % or less, or 15 mass % or less, from the viewpoint of further increasing the thermal conductivity, and may be 5 mass % or more, from the viewpoint of increasing the flexural strength of the silicon nitride sintered body.
[0035] The raw material powder may contain a sintering aid in addition to silicon nitride. As the sintering aid, an oxide-based sintering aid can be used. As the oxide-based sintering aid, YO 3、 Examples include MgO and Al2O3. The content of oxide-based sintering aids in the raw powder is such that high thermal conductivity and excellent insulation properties can be achieved at a high level. Silicon nitride From the viewpoint of obtaining a sintered body, the content may be, for example, 4.0 to 8.0 mass %, or may be 4.0 to 5.0 mass %.
[0036] The raw material powder is pressed at a molding pressure of, for example, 3.0 to 10.0 MPa to obtain a molded body. The molded body may be produced by uniaxial pressing or by CIP. Also, the molded body may be fired while being molded by hot pressing. The molded body may be fired in an inert gas atmosphere such as nitrogen gas or argon gas. The pressure during firing may be 0.7 to 0.9 MPa. The firing temperature may be 1860 to 2100°C, or may be 1880 to 2000°C. The firing time at the firing temperature may be 6 to 20 hours, or may be 8 to 16 hours. The heating rate up to the firing temperature may be, for example, 1.0 to 10.0°C / hour.
[0037] FIG. 2 is a schematic diagram showing the grain growth during sintering of silicon nitride particles in the manufacturing method of this embodiment. β-SiN has a higher melting point than α-SiN, and grain growth is slower. Therefore, when the α-phase ratio of silicon nitride contained in the raw material powder is low, grain growth proceeds more slowly than when the α-phase ratio is high. Therefore, defects remaining in the grains are suppressed during the grain growth of silicon nitride, and as a result, a silicon nitride sintered body with fewer defects is obtained as shown in FIG. 2. Such a silicon nitride sintered body has high thermal conductivity and high fracture toughness.
[0038] FIG. 6 is a schematic diagram showing the grain growth during sintering of silicon nitride particles in a conventional manufacturing method. In FIG. 6, the alpha conversion rate of silicon nitride in the raw powder is higher than that in FIG. 2. Therefore, in the grain growth process of silicon nitride, alpha-SiN proceeds to complement the grain growth of beta-SiN, so that the grain growth rate of silicon nitride is faster. As a result, the number of defects remaining in the grains in the finally obtained silicon nitride sintered body is greater than that in FIG. 2. Such a silicon nitride sintered body has a lower thermal conductivity and fracture toughness than the silicon nitride sintered body obtained in FIG. 2.
[0039] Defects contained in the silicon nitride sintered body may include lattice defects such as dislocations, pores, etc. The porosity of the silicon nitride sintered body of the present embodiment may be, for example, 1.0 volume % or less, or 0.5 volume % or less.
[0040] FIG. 3 is a graph showing an example of the change in relative density of a silicon nitride sintered body depending on the firing temperature. In FIG. 3, curve 1 shows the change in relative density when a raw material powder containing silicon nitride with an alpha-phase ratio of 15 mass% is used. On the other hand, curve 2 shows the change in relative density when a raw material powder containing silicon nitride with an alpha-phase ratio of 93 mass% is used. As shown in FIG. 3, when a raw material powder with a low alpha-phase ratio is used, the increase in relative density is gentle. This indicates that the grain growth rate of silicon nitride is slow. The silicon nitride sintered body obtained in this way has a sufficiently reduced number of defects. In addition, due to the crystal shape of β-SiN, it is composed of large-sized columnar crystal grains. It is considered that these factors result in high thermal conductivity and high fracture toughness.
[0041] The silicon nitride sintered body of the present embodiment has high thermal conductivity and therefore excellent heat dissipation. In addition, since it has high fracture toughness, it can be used stably for a long period of time without breaking even in a usage environment where it is subjected to a so-called thermal cycle in which high and low temperatures are repeated. Therefore, it has excellent reliability. As described above, since it has both excellent heat dissipation and excellent reliability, it can be suitably used as a substrate for a power module.
[0042] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. EXAMPLES
[0043] The present disclosure will be described in more detail with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0044] Example 1 <Preparation of sintered silicon nitride> Silicon nitride powder (Starck) with an alpha content of 15% by mass was prepared. This silicon nitride powder was mixed with sintering aids MgO and Y2O3 in a ratio of Si3N4:MgO:Y2O3 = 95.2:1.5:3.3 (mass ratio) to obtain a raw material powder. This raw material powder was uniaxially pressed at a pressure of 6.0 MPa to produce a cylindrical compact.
[0045] The molded body was placed in an electric furnace equipped with a carbon heater and heated to 1900°C at a rate of 2.1°C / hour under a nitrogen gas atmosphere (pressure: 0.88MPa). After sintering at 1900°C for 12 hours, the material was cooled at a rate of approximately 5.0°C / hour to obtain a silicon nitride sintered body. The silicon nitride content in the silicon nitride sintered body was 92 mol%.
[0046] <Evaluation of sintered silicon nitride> The thermal conductivity (20°C) of the silicon nitride sintered body was measured in accordance with JIS R 1611:2010. Thermal diffusivity A [m 2 The thermal conductivity [°C / sec] was determined by the laser flash method using a sample with dimensions of length x width x thickness = 10 mm x 10 mm x 2 mm. The measurement device used was a Netzch product (device name: LFA447). Density B was measured by the Archimedes method, and specific heat C was determined by differential thermal analysis. Thermal conductivity was calculated using the formula A x B x C. The results are shown in Table 1.
[0047] The thermal conductivity at 50 to 200°C was measured in the same manner as the thermal conductivity at 20°C, except that the thermal diffusivity A was measured at each temperature and a literature value was used as the specific heat C. These results are plotted in FIG. 4. The thermal conductivity at 20°C is also plotted in FIG. 4. As shown in FIG. 4, it was confirmed that the thermal conductivity decreases as the temperature increases. However, it was confirmed that the thermal conductivity of the silicon nitride sintered body of Example 1 was higher than that of Comparative Example 1 at all temperatures.
[0048] Fracture toughness (K IC ) is a value measured by the SEPB method, and is in accordance with JIS R1607:2015, and was measured using a commercially available measuring device (Instron, device name: Universal Testing Machine Model 5582). The results are shown in Table 1.
[0049] The flexural strength was a three-point bending flexural strength, and was measured using a commercially available flexural strength tester (manufactured by Shimadzu Corporation, device name: AG-2000) in accordance with JIS R 1601: 2008. The results are shown in Table 1.
[0050] The dielectric breakdown strength was measured in accordance with JIS C-2110:2016 using a commercially available measuring device (manufactured by Keisoku Gijutsu Kenkyusho, device name: Model 7474). The results are shown in Table 1.
[0051] The fracture surface of the silicon nitride sintered body was observed with a scanning electron microscope (SEM). Figure 5 is a photograph of the observed image by SEM (magnification: 3000 times). The proportion of columnar crystals was high.
[0052] Comparative Example 1 A silicon nitride sintered body was obtained in the same manner as in Example 1, except that a silicon nitride powder having an alpha conversion rate of 93 mass% was used and the sintering was performed for 4 hours at a sintering temperature of 1850° C. The obtained silicon nitride sintered body was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 and FIG.
[0053] The fracture surface of the silicon nitride sintered body was observed with a scanning electron microscope (SEM). Figure 7 is a photograph of the image observed with an SEM (magnification: 3000 times). The proportion of columnar crystals was lower than in Figure 5, and the crystal grain size was also smaller than in Figure 5.
[0054] [Table 1]
[0055] (Examples 2 to 4) A silicon nitride sintered body was obtained in the same manner as in Example 1, except that silicon nitride powders having an alpha conversion rate of 10 to 25 mass% were used as shown in Table 2. The obtained silicon nitride sintered body was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0056] [Table 2]
[0057] (Comparative Examples 2 to 5) As shown in Table 3, silicon nitride sintered bodies were obtained in the same manner as in Example 1, except that silicon nitride powders having an alpha conversion rate of 46 to 90 mass% were used. The obtained silicon nitride sintered bodies were evaluated in the same manner as in Example. The evaluation results are shown in Table 3.
[0058] [Table 3]
[0059] As shown in Tables 1 to 3, it was confirmed that the thermal conductivity could be increased by decreasing the alpha conversion rate of the silicon nitride powder used as the raw material powder. [Industrial Applicability]
[0060] According to the present disclosure, it is possible to provide a silicon nitride sintered body having both excellent heat dissipation properties and high reliability, and a method for producing the same. In addition, according to the present disclosure, it is possible to provide a laminate including such a silicon nitride sintered body. In addition, according to the present disclosure, it is possible to provide a laminate including the above-mentioned laminate. Power Module can be provided. [Explanation of symbols]
[0061] 10...substrate (sintered silicon nitride), 11, 12...metal layer, 30...filler, 33...electrode, 20...base plate, 22...cooling fin, 23...screw, 24...grease, 31, 32, 35...solder layer, 34...metal wire, 36...housing, 50...laminated body, 60...semiconductor element, 100...power module.
Claims
1. The method includes a step of forming and sintering a raw material powder consisting of only silicon nitride powder and a sintering aid, to obtain a silicon nitride sintered body having a fracture toughness (K IC ) of 7.4 to 15 MPa·m 1 / 2 and a flexural strength of more than 600 MPa and not more than 800 MPa, The method for producing a silicon nitride sintered body, wherein the silicon nitride powder contained in the raw material powder has an alpha conversion rate of 10 to 20 mass %.
2. The method according to claim 1, wherein the thermal conductivity (20°C) of the silicon nitride sintered body is greater than 100 W / m·K and is not more than 200 W / m·K.
3. 3. The method according to claim 1, wherein in the step, the raw material powder is molded, heated at a rate of 1.0 to 10.0° C. / hour, and fired at 1880 to 2000° C. for 8 to 16 hours.
Citation Information
Patent Citations
Method for manufacturing high-thermal-conductivity silicon nitride substrate
CN108774066A
Production of high-toughness silicon nitride sintered body
JP1990255573A
Silicon nitride powder
JP1991177307A
Method for increasing beta-fraction of powdery silicon nitride
JP1994263410A
Metallized highly heat conductive silicon nitride substrate, its production and silicon nitride module
JP1995149588A